Aryl and Heteroaryl N1‐Tetrazoles through Ligand‐Free Suzuki‐Reaction under Aerobic, Aqueous Conditions. Issue 17 (3rd May 2017) - Seifried, Marco; Knoll, Christian; Giester, Gerald; Welch, Jan M.; Müller, Danny; Weinberger, Peter
Abstract : Substituted 1‐biaryl‐1 H ‐tetrazoles are classically obtained from the corresponding 1‐aminobiaryls, limiting the selection of substrates. The development and substrate scope of a green, ligand‐free Suzuki protocol in aqueous media under ambient atmosphere, leading to 1‐biaryl‐ and heteroaryl‐substituted 1 H ‐tetrazoles in very good to excellent yields is presented. The combination of PdCl2 /NEt3 /H2 O/EtOH was found to combine high yields and high purity for all substrates investigated. Comparative experiments investigating the reaction rate showed that the tetrazole does not act as a ligand for the palladium catalyst. Abstract : The development and substrate scope of a green, ligand‐free Suzuki protocol in aqueous media under ambient atmosphere, leading to 1‐biaryl‐ and heteroaryl‐substituted 1 H ‐tetrazoles in very good to excellent yields is presented.